Pay and networks in organizations: Incentive redesign as a driver of network change. (3rd September 2021) - Mitsuhashi, Hitoshi; Nakamura, Azusa
Abstract: Research summary: We examine how corporate innovators adapt their intraorganizational networks when firms introduce performance‐based incentive plans that center on the short‐term achievement of individuals' measurable outputs. We postulate that such plans prompt individuals to revise goals and reconfigure their networks accordingly. Using the co‐patenting data, we analyzed cases of this incentive redesign by Japanese electronics firms in the 1990s. We found that the redesign engendered the emergence of more closed and smaller networks in organizations. Although inconsistent, we found some evidence that it promoted corporate innovators to build networks with others with similar expertise. These findings support the notion of incentive‐induced network adaptation and suggest a new theme to study the effects of incentive redesign on network evolution. Managerial summary: Research suggests that innovators' networks assist with generating novel ideas, and that some structural characteristics encourage innovation. However, knowledge about how managers can create social conditions that promote the emergence of "ideal" networks in their firms is limited. We focus on the effects of incentive redesign and explore how corporate innovators can change their intraorganizational networks when firms introduce performance‐based incentive plans. We found that the redesign engendered the emergence of more closed and smaller networks in organizations. We also obtained some evidence that suggests that the redesign prompts inventors to include those with similar expertise in their networks. Thus, it is possible that managers can use incentive plans to design innovation networks in organizations.